Ignition : what you can do to fight global warming and spark a movement - Isham, Jonathan; Waage, Sissel A. (Island Press, 2007)
Ignition brings together some of the world's finest thinkers and advocates to jump start the ultimate green revolution. Including celebrated writers like Bill McKibben and renowned scholars like Gus Speth, as well as young activists, the authors draw on direct experience in grassroots organization, education, law, and social leadership. Their approaches are various, from building coalitions to win political battles to rallying shareholders to change corporate behavior. But they share a belief that private fears about deadly heat waves and disastrous hurricanes can translate into powerful public action. For anyone who feels compelled to do more than change their light bulbs or occasionally carpool, Ignition is an essential guide. Combining incisive essays with success stories and web resources, the book helps readers answer the most important question we all face: "What can I do?"